(untitled) (The Research of Medical Science Review, 2025)
Objective: The frequency of weight gain in patient taking olanzapine would also be determined. Background: Olanzapine is a drug that belongs to the atypical antipsychotics and is most widely used for the treatment of schizophrenia and bipolar disorder. However, it is linked with some amount of additional weight that poses different health risks to an individual. It is imperative to know more about the likelihood that patients under olanzapine will gain weight to introduce timely action. Methodology: The research sample comprised 159 patients taking olanzapine in the Khyber Teaching Hospital in Peshawar, Pakistan. As the research method of the study, non-probability consecutive sampling was adopted. Demographic, clinical characteristics and laboratory variables were obtained with a special emphasis on weight alterations during treatment. After completing the data analysis, the study employed software known as IBM SPSS – version 24 for Windows; the study employed means, frequencies, and Chi-Square tests to analyze the various variables. Results: Of patients taking olanzapine, 70.4% gained weight, and 42.3% of the patients’ weights increased by over 5 percent from baseline. Analyzing the data with the help of statistical methods, it was found that there is a relationship between the length of the administration of olanzapine and weight increase (p < 0,05). Conclusion: It reveals that the incidence of weight gain with olanzapine is high, which demands weight monitoring and timely interventions to minimize the associated health risks.